The Relationship Between Self-Efficacy and Peer Social Support in High School Students' Career Decision-Making: A Correlational Study in Indonesia - Rahmad Firmansyah; Dina Sukma (Yayasan Nurul Yakin Bunga Tanjung, 2025)
This study examines the relationship between self-efficacy and peer social support on career decision-making among 11th-grade students at State Senior High School 1 Padang, Indonesia. Using a quantitative correlational design with a sample of 200 students selected through proportional random sampling, data were collected using validated instruments and analyzed through multiple regression. The results indicate that both variables collectively explain 51.8% of variance in career decision-making (R² = 0.518), with self-efficacy demonstrating a significant positive effect (β = 0.839, p < 0.001) while peer social support shows a significant negative effect (β = -0.207, p < 0.001). These findings reveal the paradoxical nature of peer influence in career decision-making within collectivistic cultural contexts, suggesting that while self-efficacy enhances career decision capability, excessive peer social support may potentially undermine students' autonomous decision-making. The study provides important implications for developing culturally-responsive career guidance interventions that simultaneously strengthen self-efficacy while teaching students to constructively navigate peer influences